Pattern of Ovarian Pathologies - Javed Iqbal, Aurangzaib, Azra Naseem, Afshan Shahid (Journal of Rawalpindi Medical College, 2013)
Background: To study frequency and pattern of ovarian pathologies. Methods: In this descriptive study patients with ovarian lesions were included. Specimen were saved in formalin and histopathological examination was performed. Results: Amongst the total 99 cases, non neoplastic ovarian lesions were found in 36.4%,benign ovarian tumours in 39.4% and malignant ovarian tumours in 24.2%. Follicular cysts (61.1%) were the commonest among non neoplastic ovarian lesions followed by luteal cyst (19.4%). Serous cystadenoma (38.5%) was the most common benign tumour followed by mature cystic teratoma (30.8%). Surface epithelial tumors were the most identified category(64.3%) followed by germ cell tumours (21.4%). Serous cystadenocarcinoma (33.3%) was diagnosed as the most common malignant ovarian tumour followed by granulosa cell tumours (25%). Conclusion: Follicular cysts are the commonest non neoplastic ovarian lesion. Serous cystadenoma is the commonest benign ovarian tumour and serous cyst adenocarcinoma is the commonest malignant tumour. Surface epithelial tumours are the most common category of tumours